Caribbean air transport : strategic options for improved services and sector performance - Andrew, Douglas R. (World Bank [Washington]US, 2006)
Seeks to provide guidance on available strategic options with regard to improving sector policy and regulation for air services and the future role of regionally owned and operated airlines and the contribution of governments thereto.